# How to you solve 1-(2/5 + 1/5)N/A

### 6 Answers | Add Yours

Whenever you are solving an equation, you have to do the part that is inside the parenthesis first. So in this case, you have to add 2/5 and 1/5. That, of course, gets you 3/5. You can just add the top parts of the fraction together as long as the bottom parts are the same.

So now the equation is simply 1-3/5. Of course, 1 is equal to 5/5. So you can write this as 5/5-3/5. Again, you can simply subtract the top parts of the fractions as long as the bottom parts are the same.

That comes out to 2/5, which is the answer to this question as a whole.

A general rule is to always solve what is in the parenthesis first. Here you are adding 2/5 to 1/5. The answer would be 3/5. Now you are going to take the first part of the equation which is 1 and subtract 3/5. Your answer would be 2/5.

Say for example the parenthesis said (6/15 - 1/5). In this case you would need to find a common denominator which in this case it is 15. You want the denominators to be the same. Let's change 1/5 so it's denominator is 15. By multiplying 5 times 3 you get fifteen. What you do to the top you have to do to the bottom so you will multiply 1 times 3. What is inside the parenthesis now looks like this: (6/15 - 3/15). This equals 3/15 which is the same as 1/5.

**1-(2/5 + 1/5)**

Lets take 1-(2/5 + 1/5)=x

Therefore, x= 1-(2/5 + 1/5)

In order to solve any Math problem, we need to always keep in mind the BODMAS rule. Therefore, in this problem, we first solve the brackets by taking L.C.M. of the values inside the bracket and adding them up, and so on.

x=1-{(2+1)/5}

x=1-(3/5)

We convert 3/5 into decimal form:

x=1-0.6

**x=0.4 **or** x=2/5**

To solve the addition or subtracion of fractions you have to convert all the fractions with the equivalent fractions with the same or equal denominators.

Go for the bracketted expression, where the two terms could be added in the numerator as both has the same or equal denominator 5. You can add the numerator and retain the denominator. So 2/5+1/5 = (2+1)/5 =3/5.

Next step:

1-(2/5+1/5) = 1-3/5.

convert 1 and 3/5 int equivalent fractions of same denominator:

1 = 1/1 = 1*5/(1*5) =5/5. Therefore,

1-3/5 = 5/5-3/5 = (5-3)/5 = 2/5

first add 2/5 + 1/5 which is 3/5. Then take 1, or 5/5 - 3/5 and the answer is 2/5.

Suppose the probable figure is x

x= 1-(2/5+1/5)

or, x=1-{(2+1)/5}

or, x=1-3/5

or, x= (5-3)/5

or, x=2/5

So, the answer is 2/5. (Ans.)